Zoledronic Acid Treatment in Primary Bone Marrow Edema Syndrome. (2nd January 2017) - Flores-Robles, Bryan Josué; Sanz-Sanz, Jesus; Sanabria-Sanchinel, Adel Abel; Huntley-Pascual, Dixie; Andréu Sánchez, José Luis; Campos Esteban, José; Blanco, Ricardo; Merino-Argumanez, Carolina; Espinosa-Malpartida, Maria; Ramos-Giráldez, Maria Consuleo; Godoy-Tundidor, Hildegarde; Jiménez-Palop, Maria Mercedes; et al.
ABSTRACT: Primary bone marrow edema syndrome (BMES) is characterized by the combination of joint pain and distinctive magnetic resonance imaging changes. It has been suggested that the use of bisphosphonate drugs reduce symptom severity. Our objective was to review cases of patients diagnosed with BMES in the last 7 years who had been treated with zoledronic acid. Access to a pharmaceutical database was gained in order to obtain a list of zoledronic acid prescriptions. Based on clinical and MRI criteria for BMES, patients were selected. Baseline pain intensity was evaluated on a scale of 0 to 3 and was also assessed after 3 and 12 months. Functional recovery was evaluated by noting if a patient had returned to carrying out his or her normal daily activities. Out of 633 patients, 17 cases of BMES were identified (8 men), with a median age of 54 ± 14.1 years. The most frequently affected joint was the ankle (9), followed by the hip. Sixteen patients presented with moderate to severe pain initially. Of those patients, 13 had no pain after 12 months. Zoledronic acid is a option in the management of BMES, since 75% of patients treated with it presented with a complete response.